IMPLIKASI KADAR AIRTANAH TERHADAP DAYADUKUNG TANAH DI WILAYAH GAMBIR DAN SEKITARNYA - Yuda, Himmes Fitra; Zakaria, Zufialdi; Sukiyah, Emi (Bulletin of Scientific Contribution, 2017)
ABSTRACTThe research area is in Gambir and surround it, Central Jakarta and West Jakarta municipality. The study to learn the characteristics of the soil in the research area. The relationship of water content and soil bearing capacity is known from secondary data of soil investigation at four locations sampled. Based on observations of four soil samples, the highest water content is in sample HF-3 at 68.28%, and the lowest water content is in sample HF-4 by 48%. Depend on the soil bearing capacity value, sample HF-3 has the lowest value, which is 2.64 T / M2. The highest soil bearing capacity value is found in the sample HF-4, which is 25.49 T / M2. Regression correlation test results showed that in dry conditions / low water content, the value of soil bearing capacity will be high, meanwhile in wet conditions, water levels will rise, so the value of the soil bearing capacity will be smaller than in dry conditions. Keywords : Soil bearing capacity, water content ABSTRAKLokasi penelitian berada pada wilayah Gambir dan sekitarnya, kotamadya Jakarta Pusat dan Jakarta Barat. Studi ini untuk mempelajari karakteristik tanah pada daerah penelitian. Hubungan kadar air dan daya dukung tanah diketahui dari data penyelidikan tanah di 4 lokasi sampel. Berdasarkan pengamatan dari 4 sampel tanah, nilai kadar air tertinggi adalah pada sampel HF-3 sebesar 68,28%,  nilai kadar air terendah adalah pada sampel HF-4 sebesar 48%. Jika dilihat dari nilai dayadukung tanah, sampel HF-3 memiliki nilai yang paling rendah, yaitu sebesar 2,64 T/M2. Nilai dayadukung tanah yang tertinggi ada pada sampel HF-4 sebesar 25,49 T/M2. Dari hasil uji regresi korelasi menunjukan bahwa pada kondisi kering/kadar air rendah, nilai dayadukung tanah akan besar, sementara pada kondisi basah, kadar air akan meningkat, sehingga nilai dayadukung tanah akan menjadi lebih kecil dibandingkan dengan kondisi kering. Kata Kunci : Dayadukung tanah, kadar air